2008
DOI: 10.1149/1.2823038
|View full text |Cite
|
Sign up to set email alerts
|

Improvements on Interface Reliability and Capacitance Dispersion of Fluorinated ALD-Al[sub 2]O[sub 3] Gate Dielectrics by CF[sub 4] Plasma Treatment

Abstract: The characteristics of atomic layer deposited ͑ALD͒-Al 2 O 3 gate dielectrics with CF 4 plasma surface treatment have been studied in this paper. Fluorine atoms were observed to be incorporated at bulk Al 2 O 3 and pile-up at both Al/Al 2 O 3 and Al 2 O 3 /Si interfaces. X-ray photoelectron spectroscopy analysis demonstrated that Al-O bonds were replaced by Al-F and F-Al-O bonds as samples were treated in CF 4 plasma. A physical model was proposed to explain the capacitance-equivalent-thickness ͑CET͒ degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…The small hysteresis of about 0.25 V, which was determined by the flat voltage difference (¦V FB ) of the curves measured by positive and negative sweeping, is attributed to the low density of interface trap charges and/or oxide trap charges. [17][18][19] Furthermore, using ® FE = g m L/(WC MOS V DS ), the maximum field-effect mobility of 170 cm 2 V ¹1 s ¹1 is extracted from transfer properties [see Fig. 3(b)] when the SAG-MOSFET works at the linear region (V d = 0.1 V), which is comparable to the values reported by others.…”
supporting
confidence: 76%
“…The small hysteresis of about 0.25 V, which was determined by the flat voltage difference (¦V FB ) of the curves measured by positive and negative sweeping, is attributed to the low density of interface trap charges and/or oxide trap charges. [17][18][19] Furthermore, using ® FE = g m L/(WC MOS V DS ), the maximum field-effect mobility of 170 cm 2 V ¹1 s ¹1 is extracted from transfer properties [see Fig. 3(b)] when the SAG-MOSFET works at the linear region (V d = 0.1 V), which is comparable to the values reported by others.…”
supporting
confidence: 76%
“…Overall, they can be categorized into two major approaches based on the reaction mechanism during the preparation: CVD and PVD-based process. CVD-based approaches mainly include metalorganic chemical vapor deposition (MOCVD) [70,71], plasma-enhanced chemical vapor deposition (PECVD) [72,73], atomic-layer chemical vapor deposition (ALCVD) [74][75][76][77][78][79], and photo-assisted CVD synthesis [80][81][82][83][84]. These growth methods provide more flexible synthesis process and an alternative to achieve lower cost.…”
Section: Methods To Deposit High-k Gate Dielectricsmentioning
confidence: 99%
“…Terai et al reported that the incorporation of fluorine ions into the SiON/Si interface reduced the interface states and decreased the negative-bias temperature instability (NBTI) because of the high binding energy of the Si-F bond [5]. In our previous studies [6], [7], we were able to improve the electrical characteristics (e.g., hysteresis and breakdown voltage) and the reliability of both HfO 2 and Al 2 O 3 by fluorine incorporation. In this letter, we both reduced the NBTI degradation and improved the electrical characteristics of HfMoN/Gd 2 O 3 p-channel metal-oxide-semicondcuctor field-effect transistors (pMOSFETs) by fluorine-ion implantation.…”
Section: Introductionmentioning
confidence: 64%